(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2019)
By definition, immigration has a very close connection to human trafficking and migrant smuggling. In recent years, the increase of international immigration flows have been accompanied by a boost on human traffi cking and migrant smuggling. This paper critically discusses the Convention against Transnational Organized Crime and its Protocols, stressing the importance of a protective legal framework concerning victims of human trafficking and smuggled migrants.